Exploring organizational crises from a legitimation perspective: Results from a computer simulation and illustrative cases - Heiko Breitsohl (University of Wuppertal, Schumpeter School of Business and Economics, 2008)
Organizational crises are rare, yet they fundamentally influence the evolution of organizations. An aspect of crises deserving more attention is the interaction of organizations and their stakeholders during a crisis from a legitimation perspective. This paper presents a simulation model mapping causal relationships behind this interaction. Results suggest that the nature and timing of organizational response to crises has considerable effect on the success and duration of attempts of regaining organizational legitimacy after a threatening event. Illustrative case studies demonstrate how several organizations have been (un-)successful in overcoming individual crises with respect to these influences.
urn:nbn:de:hbz:468-20080556
Keywords: 330; Organisation; Krisenmanagement; Organisatorischer Wandel; Simulation; Theorie